P13 | MORPHO-FUNCTIONAL DIFFERENCES IN THE GUT OF AGED MICE WITH THE POSSIBLE EFFECTS OF ANTI-INFLAMMATORY TREATMENTS (European Journal of Histochemistry)
The gastrointestinal (GI) barrier represents one of the most important interfaces between organism and the external environment with a continue exposure to external substances1. For these reasons, preserving the structural and functional integrity of the GI barrier is fundamental to control and prevent inflammation, which contributes to age-related diseases2. Evidence suggests associations between the inflammation/ senescence and the presence of chronic disease in the elderly, thus the aim of the study has been to evaluate the morpho-functional differences in the intestinal wall of aged mice with or without an anti-inflammatory treatment. We used C57BL/6J mice intranasal treated with vehicle (control) or IL4-EVs (extracellular vesicles released by anti-inflammatory microglia stimulated with IL-4) to reduce the inflammatory phenotype of microglia3. We evaluated the gut transit and the inflammatory factors in plasma, such as IL16, CCL2 and TIMP1. Then we performed hematoxylin & eosin (H&E) and periodic acid-Schiff (PAS) staining to describe the differences in the morphological aspects of the intestinal wall. In the end, we investigated the changes in permeability through occludin expression and the presence of specific nervous markers such as Glial Fibrillary Acidic Protein (GFAP) and α-synuclein (αsyn) to better characterize the possible connections between the enteric nervous system (ENS) and the aging.4 IL-4- EVs increase the gut transit and reduce inflammatory factors in plasma. Upon the treatment, we found changes in: (i) villus’s dimension, (ii) quantity of goblet cells, (iii) architecture of occludin, and (iv) the co-expression of GFAP/α-syn. Since IL-4-EVs are capable to modify inflammatory profile in late adult mice, they could play a role in the gut-brain axis in aged mice and in the inflammatory process acting in the tight relationship between permeability of the intestinal barrier and the enteric glial cells.